A randomized study of intensified antiretroviral treatment monitoring versus standard-of-care for prevention of drug resistance and antiretroviral treatment switch. (15th November 2022) - Hermans, Lucas E.; Ter Heine, Rob; Schuurman, Rob; Tempelman, Hugo A.; Burger, David M.; Vervoort, Sigrid C.J.M.; Deville, Walter L.J.M.; De Jong, Dorien; Venter, Willem D.F.; Nijhuis, Monique; Wensing, Annemarie M.J.
Abstract : Introduction: Standard-of-care antiretroviral treatment (ART) monitoring in low and middle-income countries consists of annual determination of HIV-RNA viral load with confirmatory viral load testing in case of viral rebound. We evaluated an intensified monitoring strategy of three-monthly viral load testing with additional drug exposure and drug resistance testing in case of viral rebound. Methods: We performed an open-label randomized controlled trial (RCT) at a rural South African healthcare clinic, enrolling adults already receiving or newly initiating first-line ART. During 96 weeks follow-up, intervention participants received three-monthly viral load testing and sequential point-of-care drug exposure testing and DBS-based drug resistance testing in case of rebound above 1000 copies/ml. Control participants received standard-of-care monitoring according to the WHO guidelines. Results: Five hundred one participants were included, of whom 416 (83.0%) were randomized at 24 weeks. Four hundred one participants were available for intention-to-treat analysis. Viral rebound occurred in 9.0% (18/199) of intervention participants and in 11.9% (24/202) of controls ( P  = 0.445). Time to detection of rebound was 375 days [interquartile range (IQR): 348–515] in intervention participants and 360 days [IQR: 338–464] in controls [hazard ratio: 0.88 (95% confidence interval (95% CI): 0.46–1.66]; P  = 0.683]. Duration of viral rebound was 87 days [IQR: 70–110] in intervention participants and 101 days [IQR: 78–213] in controls ( P  = 0.423). In the control arm, three patients with confirmed failure were switched to second-line ART. In the intervention arm, of three patients with confirmed failure, switch could initially be avoided in two cases. Conclusion: Three-monthly viral load testing did not significantly reduce the duration of viraemia when compared with standard-of-care annual viral load testing, providing randomized trial evidence in support of annual viral load monitoring.